Explosion Gas Bubbles Near Simple Boundaries - James E. Chisum; Young S. Shin (Shock and Vibration)
Finite element analyses of explosion gas bubbles show that including the compressibility of the surrounding media leads to appreciable differences in key areas of the bubble’s behavior. In order to more fully understand the behavior of bubbles created by detonations near simple boundaries, analyses incorporating fluid compressibility were conducted at various stand-off distances from simple rigid and constant pressure surface boundaries. The results from these analyses serve to characterize the behavior of the bubbles for the charge type, charge weight, and hydrostatic pressure used in the analyses.